Занимательная физиология растений - Артамонов Вадим Иванович (Агропромиздат, 1991)
Экземпляры: ф15 (20231201) / Инвентарный номер: 25309 / Цена: 2.30 / Сис.шифр: 28.5 / Авт.знак: А 86 / ГРНТИ: 34 / ББК: 28.5